Toxic effect of elements on the germination and initial development of barley seeds (Hordeum vulgare L.) - Leite, Ranyele Renata; Menezes Filho, Antonio Carlos Pereira de; Carlos, Leandro; Sharma, Porshia; Ventura, Matheus Vinicius Abadia; Castro, Carlos Frederico de Souza; Teixeira, Marconi Batista; Soares, Frederico Antônio Loureiro; Nuñez, Daniel Noe Coaguila (Brazilian Journal of Science, 2024)
Barley (Hordeum vulgare) is an agricultural vegetable from the Poaceae family used in food and beer production. The study aimed to evaluate the toxic effect of Aluminum (Al) and Copper (Cu) on germination and initial development in barley seeds cultivar KWS Irina. Different concentrations (0, 35, 85 and 125 mg L-1) of aqueous solution of Al and Cu were produced from their chlorides. The toxicity experiment was carried out in a germination box maintained in a germination chamber with a 12-h photoperiod. After 15 days of germination, the seedlings were measured using a millimetric ruler (cm) where they were evaluated for plant length, root length, and fresh and dry mass of plant and root determined on a digital analytical scale (g). Barley seedlings cultivar KWS Irina demonstrated to be intolerant to concentrations of the toxic elements Al and Cu in all plant parameters analyzed, except for plant dry mass. Future studies should be carried out comparing the initial and reproductive development of this barley cultivar in terms of the presence and absence of toxic elements.